Mestni odprti prostori kot rekreacijska območja in zatočišča v primeru izrednih razmer - Pouya Sönmez, Sahar (Urbani izziv, 2025)
Public open spaces (POSs) played an important role as gathering areas during the 2023 earthquake in Turkey. However, challenges arose after the earthquake because POSs struggled to fulfil their recreational functions and could not meet the daily needs of the population. This study evaluates the performance of and changes to six POSs in Malatya after the earthquake and suggests strategies for integrating sustainability principles into seismic protection plans. The post-occupancy evaluation method was used, including field analysis, semi-structured interviews with sixty municipal experts, and a survey with 240 users. The results show that POSs faced problems such as insufficient infrastructure, limited space for camps, and issues related to safety and maintenance during the earthquake. After the earthquake, most POSs had not regained their recreational identity, with some transforming toward commercial use, occupation by new users, and changes in land use. The study concludes that earthquake resilience depends not only on the size, accessibility, and location of a POS, but also on the area’s capacity for rapid maintenance and its multifunctionality, which ensure its vitality after a disaster. Planning recommendations include integrating disaster preparedness into city planning and facilitating post-disaster restoration.
Keywords: ARAS; avtobusna postaja; earthquake resilience; izbor lokacije; Malatya; MOOSRA; post-disaster recovery; public open spaces (POSs); Turkey; večkriterijska analiza; VIKOR